Features Associated With Metastases Among Well-Differentiated Neuroendocrine (Carcinoid) Tumors of the Appendix: The Significance of Small Vessel Invasion in Addition to Size. Issue 12 (December 2015) - Kleiman, David A.; Finnerty, Brendan; Beninato, Toni; Zarnegar, Rasa; Nandakumar, Govind; Fahey, Thomas J.; Lee, Sang W.
Abstract : BACKGROUND: The risk of metastatic disease among carcinoid tumors of the appendix increases with tumor size. However, it is unclear if any features other than size are also associated with an increased risk of metastatic disease. OBJECTIVE: The aim of this study was to review the characteristics of appendiceal carcinoid tumors and determine if other histologic features besides size should guide surgical decision making. DESIGN: This study involved a retrospective case series. SETTINGS: This study was conducted at a single tertiary acute care hospital. PATIENTS: Patients diagnosed with an appendiceal carcinoid tumor between 2000 and 2014 were identified. Goblet cell carcinoids, adenocarcinomas with neuroendocrine features, and tumors from other primary locations were excluded. INTERVENTIONS: Simple appendectomy or segmental/total colectomy with lymphadenectomy was performed. MAIN OUTCOME MEASURES: The primary outcomes measured were metastases, recurrence, and overall survival. RESULTS: Seventy-nine patients were included. The overall incidence of metastatic disease was 10%. Patients with metastatic disease were more likely to be male (75% vs 28%, p = 0.008), have small-vessel invasion (43% vs 5%, p = 0.001), and have larger tumors (median 2.0 cm vs 0.5 cm, p < 0.001). Among tumors <2 cm, the incidence of metastases among tumors with small-vessel invasion was 60% compared with 0% among those without small-vessel invasion ( p < 0.001). Among tumors ≥2 cm, the incidence of metastases was 50% irrespective of small-vessel invasion. If small-vessel invasion was used as a second indication for performing a right hemicolectomy along with size ≥2 cm, both the sensitivity and negative predictive value would have been 100% compared with 63% and 96% if size was used alone. Patients with metastatic disease had a higher incidence of recurrence (13% vs 0%, p = 0.003), but overall survival was 100% in both groups. LIMITATIONS: Small sample size, retrospective design, and limited long-term follow-up were the limitations of this study. CONCLUSIONS: Carcinoid tumors of the appendix <2 cm with small-vessel invasion have similar metastatic potential as tumors ≥2 cm. Therefore, a recommendation for a right hemicolectomy should be considered for tumors <2 cm with small-vessel invasion. Additional prospective multicenter studies are warranted.